Wormhole-induced effective coupling in SYK chains - Pablo Basteiro; Giuseppe Di Giulio; Johanna Erdmenger; René Meyer; Zhuo-Yu Xian (Journal of High Energy Physics)
Abstract Inhomogeneous quantum chains have recently been considered in the context of developing novel discrete realizations of holographic dualities. To advance this programme, we explore the ground states of infinite chains with large number N of Majorana fermions on each site, which interact via on-site q-body Sachdev-Ye-Kitaev (SYK) couplings, as well as via additional inhomogeneous hopping terms between nearest-neighbour sites. The hopping parameters are either aperiodically or randomly distributed. Our approach unifies techniques to solve SYK-like models in the large N limit with a real-space renormalization group method known as strong-disorder renormalization group (SDRG). We show that the SDRG decimation of SYK dots linked by a strong hopping induces an effective hopping interaction between their neighbouring sites. If two decimated sites are nearest neighbours, in the large q limit their local ground states admit a holographic dual description in terms of eternal traversable wormholes. At the end of the SDRG procedure, we obtain a factorised ground state of the infinite inhomogeneous SYK chains that we consider, which has a spacetime description involving a sequence of wormholes. This amounts to a local near-boundary description of the bulk geometry in the context of discrete holography.